Anonymization in Social Networks: A Survey on the issues of Data Privacy in Social Network Sites (International Journal of Engineering and Computer Science, 2017)
Recent years have seen unprecedented growth in the popularity of social network systems. Social networks are online applications which allow its users to connect by various link types. Online social networks, such as Facebook, LinkedIn are progressively utilized by many people. It makes digital communication technologies sharpening tools for extending the social circle of people. It has already become an important integral part of our daily lives, enabling us to contact our friends and families on time. As social networks have developed rapidly, recent research has begun to explore social networks to understand their structure, advertising and marketing, and data mining online population, representing 1.2 billion users around the world. More and more social network data has been made publicly available and analyzed in one way or another.